Influence of Step Rate and Quadriceps Load Distribution on Patellofemoral Cartilage Contact Pressures during Running - Lenhart, Rachel L. (J Biomech, 2015)
Interventions used to treat patellofemoral pain in runners are often designed to alter patellofemoral mechanics. This study used a computational model to investigate the influence of two interventions, step rate manipulation and quadriceps strengthening, on patellofemoral contact pressures during running. Running mechanics were analyzed using a lower extremity musculoskeletal model that included a knee with six degree-of-freedom tibiofemoral and patellofemoral joints. An elastic foundation model was used to compute articular contact pressures. The lower extremity model was scaled to anthropometric dimensions of 22 healthy adults, who ran on an instrumented treadmill at 90%, 100% and 110% of their preferred step rate. Numerical optimization was then used to predict the muscle forces, secondary tibiofemoral kinematics and all patellofemoral kinematics that would generate the measured hip, knee and ankle joint accelerations. Mean and peak patella contact pressures reached 5.0 and 9.7 MPa during the midstance phase of running. Increasing step rate by 10% significantly reduced mean contact pressures by 10.4% and contact area by 7.4%, but had small effects on lateral patella translation and tilt. Enhancing vastus medialis strength did not substantially affect pressure magnitudes or lateral patella translation, but did shift contact pressure medially toward the patellar median ridge. Thus, the model suggests that step rate tends to primarily modulate the magnitude of contact pressure and contact area, while vastus medialis strengthening has the potential to alter mediolateral pressure locations. These results are relevant to consider in the design of interventions used to prevent or treat patellofemoral pain in runners.